The effect of using albumin-perfluorohexane/cisplatin-magnetite nanoparticles produced by hydrothermal method against gastric cancer cells through combination therapy - Dongsheng Li; Yue Fan; Miaomiao Liu; SiLin Huang; Shasha Wang (Arabian Journal of Chemistry, 2023)
Because magnetic nanoparticles (NPs) have the ability to combine different therapies such as drug delivery and photothermal therapy (PTT) along with reducing cancer drug resistance, their use in cancer treatment is considerable. For this purpose, we developed albumin-perfluorohexane/cisplatin-magnetite NPs (A-PFH/C-MNPs) by hydrothermal method. Then, the physicochemical properties of the MNPs and A-PFH/C-MNPs were investigated by SEM, TEM, XRD, and FTIR. In the following, drug release at different pH and A-PFH/C-MNPs thermal reactions were assessed. The toxicity of different drug formulations against advanced gastric cancer (AGS) and mouse fibroblast (3 T3) cells were assessed by MTT assay, followed by flow cytometry and real time PCR on AGS cells. The results determined that A-PFH/C-MNPs (∼142 nm) with a relatively uniform distribution, in addition to increasing the loading capacity up to 60%, raise the PFH release by increasing the temperature from 37 °C to 45 °C. Also, in vitro outcomes exhibited higher toxicity of A-PFH/C-MNPs + PTT compared to free C against AGS cells. Whereas, the toxicity of A-C-MNPs and A-PFH/C-MNPs + PTT on 3 T3 cells as normal cells was much lower compared to the cancer cells. The mechanism of cytotoxicity indicates that A-PFH/C-MNPs + PTT significantly increase apoptosis by inducing expression of TNF-α and Bax mRNA compared to A-C-MNPs. Overall, A-PFH/C-MNPs + PTT provided a promising platform in anticancer activity by increasing drug loading capacity and combined chemotherapy and PTT.